Design Optimization of 3-phase rectifier power transformers by Genetic Algorithm and Simulated Annealing - K.S., Rama Rao; K.N., Mohd Hassan (2008)
This paper presents the design optimization, by Genetic Algorithm (GA) and Simulated Annealing (SA), of a 3-phase rectifier power transformer supplying a dc load. A closed form expression for actual phase current waveform of the rectifier transformer is used and a comparison is made with the approximate waveform normally considered for fixing the transformer rating. Two non-linear programming techniques, GA and SA are applied for the estimation of transformer design parameters and the results are compared. The optimal results demonstrated by an example show the potential for implementation of GA as an efficient search technique for design optimization of transformers. A discussion on the limitations and variation of GA parameters while minimizing the single and multi-objective functions satisfying the performance constraints on the proposed optimal design concludes the paper.